Spiritual Emotional Freedom Technique (Seft) As Implementation Of Nursing Care In Hypertension Patients With Lower Of Blood Pressure - Sholichin; Mayusef Sukmana; Iskandar Muda; Kharunisa Az Zahra (Mulawarman Nursing Indonesia Journal, 2023)
Background: Hypertension is a non-communicable disease, and this degenerative disease is widespread, has a high mortality rate, and affects a person's quality of life and productivity. High blood pressure or hypertension is often called The Silent Killer because this disease is a hidden killer. Hypertension is defined as a condition that shows the results of an examination where the systolic blood pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg or more on two measurements with an interval of five minutes in a state of sufficient rest/calm. Treatment of hypertension can be done in two ways. Namely pharmacological and nonpharmacological. One of the nonpharmacological therapies that can be used is SEFT. Purpose: The purpose of this study was to find out the description of SEFT therapy in reducing blood pressure in hypertensive patients Method: This research design uses a descriptive research design with a case study approach. The sampling technique is purposive sampling which will be carried out in June-July 2022 with three respondents. Results: The study of 3 respondents showed different results—the average decrease in blood pressure of respondent 1 in Ny. M the difference is the systolic pressure of 8 mm Hg and the diastolic pressure of 15 mm Hg in respondent 2 Ny. The difference S is the systolic pressure of 10 mmHg and the diastolic pressure of 7 mmHg. While respondent 3 Ny. A, the difference in systolic pressure is 12 mmHg, and diastolic pressure is eight mmHg Conclusion: There was a decrease in blood pressure in respondents with SEFT therapy for three days. Researchers concluded that hypertension could not only be treated with pharmacological treatment, such as complementary therapy and SEFT therapy. Keywords: Hypertension, SEFT Therapy